2021
DOI: 10.29333/ejecs/694
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Bicultural Attitudes, Paternal Versus Maternal Acceptance, and Psychological Adjustment of Ethnic Minority Youth in Bangladesh

Abstract: The purpose of this study was to explore the effects of perceived paternal and maternal acceptance on the bicultural orientations and psychological adjustment of ethnic-minority young adults in Bangladesh. The study was based on a sample of 412 young adults (mean age 22 years), consisting of 40% women and 60% men from 18 tribal subgroups in Bangladesh. Measures used were Parental Acceptance–Rejection Questionnaire (PARQ), Bicultural Attitude Scale (BAS) and Personality Assessment Questionnaire (PAQ). Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Therefore, future studies should continue to examine the reciprocal relationships between school adjustment and bicultural acceptance over time from middle school to high school. Second, previous studies [71,72] have reported that fathers, apart from mothers, have an independent influence on their children's bicultural acceptance and school adjustment; thus, future prospective research should compare the relative influences of parents on bicultural acceptance and school adaptation among adolescents from multicultural families. Third, as parents' influence on their children's school adjustment and cultural identities was found to differ according to the children's sex in several studies [72,73], future research could compare the influence of parents' involvement in education on adolescent children's school adjustment and bicultural acceptance while considering the effect of the children's sex.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should continue to examine the reciprocal relationships between school adjustment and bicultural acceptance over time from middle school to high school. Second, previous studies [71,72] have reported that fathers, apart from mothers, have an independent influence on their children's bicultural acceptance and school adjustment; thus, future prospective research should compare the relative influences of parents on bicultural acceptance and school adaptation among adolescents from multicultural families. Third, as parents' influence on their children's school adjustment and cultural identities was found to differ according to the children's sex in several studies [72,73], future research could compare the influence of parents' involvement in education on adolescent children's school adjustment and bicultural acceptance while considering the effect of the children's sex.…”
Section: Discussionmentioning
confidence: 99%